Effects of sludge on the ash fusion behaviors of corn stalk and its modification mechanisms. (1st June 2021) - Li, Fenghai; Zhao, Wei; Fan, Hongli; Xu, Meiling; Lu, Jinfeng; Zhao, Chaoyue; Guo, Mingxi; Guo, Qianqian; Fang, Yitian
Highlights: Ash fusion temperatures (AFTs) of two sludge, corn stalk (CS) and CS mixtures were tested. The sludge additions increased the AFTs of CS mixture and mitigated its slagging tendency. Ca3 (PO4 )2 (AlPO4 ) formation with municipal sludge addition caused their AFT increase (reduce). Formations of Fe2 O3 and Fe3 O4 with increasing textile dyeing sludge proportion made their AFT increase. Abstract: The ash fusion behaviors of corn stalk (CS) and its variation mechanisms by two sludges [municipal-water sewage sludge (MW) and textile dyeing sludge (TD)] additions in an oxidizing atmosphere were investigated. Increasing the MW mass ratio led to an initial slow rise in the ash fusion temperatures (AFTs), but then they slowly decreased. The four characteristic temperatures for CS-TD all gradually increased as the TD proportion rose. An increase in the MW percentage led to changes in the generation and proportions of Ca2 MgSi2 O7, CaAl2 Si2 O8, CaMgSi2 O6, KAlSi2 O6, and Ca3 (PO4 )2, and these changes increased the AFTs. The formation of AlPO4 and its subsequent transformation into amorphous matter at high temperatures slowly decreased the AFT when the MW percentage exceeded 70%. The generations of Fe3 O4 and Fe2 O3 and the increases in their proportions as the TD percentage rose led to a gradual increase in the AFTs. The results from this study improve current understanding about the AFT variation mechanisms operating when sludge is added to CS and provide information that can be used to mitigate ash-related issues during the co-combustion of CS and sludge.